Gouverneur Morris papers - Morris, Gouverneur, 1752-1816.; Morris, Anne Cary Randolph, 1774-1837.
Letterbooks, diaries, legal and financial papers, and miscellany relating chiefly to Morris's mission to London (1790-1791) and his service as minister to France (1792-1794) and in the U.S. Senate (1800-1803). Also includes material pertaining to Morris's work as a business agent for Robert Morris, social life in Paris, the French Revolution and the Reign of Terror, Morris's New York estate Morrisania, the War of 1812, the Hartford Convention, the development of the Erie Canal, and other events of the period and financial memoranda of his wife, Anne Cary Randolph Morris.
Correspondents include William Carmichael, Lord Grenville; Alexander Hamilton; David Humphreys; Thomas Jefferson; Marie Adrienne de Noailles, marquise de Lafayette; Marie Joseph Paul Yves Roch Gilbert du Motier, marquis de Lafayette; Francis Godolphin Osborne, duke of Leeds; Robert Morris; Thomas Pinckney; William Short; and George Washington, as well as various French ministers and diplomats.
Microfilm edition of a portion of these papers available
Microfilm produced from originals in the Manuscript Division.
Lawyer, diplomat, and U.S senator from New York.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carmichael, William, -- -1795 -- Correspondence; Grenville, William Wyndham Grenville, -- Baron, -- 1759-1834 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Humphreys, David, -- 1752-1818 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Lafayette, Marie Adrienne de Noailles, -- marquise de, -- 1759-1807 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Leeds, Francis Godolphin Osborne, -- Duke of, -- 1751-1799 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Pinckney, Thomas, -- 1750-1828 -- Correspondence; Short, William, -- 1759-1849 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Canals -- New York (State); Diplomatic and consular service, American -- France; Diplomatic and consular service, French; Real property -- New York (State).; States' rights (American politics); Erie Canal (N.Y.); France -- Foreign relations -- United States; France -- History -- Revolution, 1789-1799.; France -- History -- Reign of Terror, 1793-1794.; Great Britain -- Foreign relations -- United States; Paris (France) -- Social life and customs; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; United States -- History -- 1783-1865.; United States -- History -- War of 1812.; Morrisania (N.Y. : Estate); Diplomats; Lawyers; Senators, U.S. Congress -- New York (State)